2003
DOI: 10.1046/j.1341-8076.2003.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of assisted reproductive technology cycles in patients with one or two ovaries

Abstract: The potential for success after in vitro fertilization is not impaired in women with one ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It is of interest that follow-up studies (Gosden et al, 1989) on the ovariectomized mice actually showed that they recruited a larger proportion of the remaining oocyte pool per cycle so that the total number of antral follicles was not reduced. There are conflicting data on this question in humans; several studies have reported a smaller number of retrieved mature follicles after stimulation for IVF by gonadotrophin in age-matched women with one ovary compared to those with two ovaries (Alper et al, 1985;Levitas et al, 2000;Levi et al, 2003); however pregnancy success rates did not differ after IVF.…”
Section: Rates Of Aneuploidy In Women With Reduced Oocyte Pool Sizementioning
confidence: 92%
“…It is of interest that follow-up studies (Gosden et al, 1989) on the ovariectomized mice actually showed that they recruited a larger proportion of the remaining oocyte pool per cycle so that the total number of antral follicles was not reduced. There are conflicting data on this question in humans; several studies have reported a smaller number of retrieved mature follicles after stimulation for IVF by gonadotrophin in age-matched women with one ovary compared to those with two ovaries (Alper et al, 1985;Levitas et al, 2000;Levi et al, 2003); however pregnancy success rates did not differ after IVF.…”
Section: Rates Of Aneuploidy In Women With Reduced Oocyte Pool Sizementioning
confidence: 92%
“…Fourteen were rejected as duplicate publications and another 765 studies did not investigate the effect of UO on ovarian reserve and were therefore excluded. Thirty‐seven studies were reviewed in full and assessed for eligibility . Twelve studies were then excluded: nine in non‐ART setting, two involving cancer patients and one exclusively considering women with polycystic ovaries .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were then excluded: nine in non‐ART setting, two involving cancer patients and one exclusively considering women with polycystic ovaries . In all, 25 studies were eligible for qualitative synthesis and 21 for quantitative synthesis . Quality assessment of the qualified studies for meta‐analysis employing the Newcastle‐Ottawa scale is provided in Appendix S2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations